If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x(2x + 5) = 8(x + 3)(x + -3) Reorder the terms: 4x(5 + 2x) = 8(x + 3)(x + -3) (5 * 4x + 2x * 4x) = 8(x + 3)(x + -3) (20x + 8x2) = 8(x + 3)(x + -3) Reorder the terms: 20x + 8x2 = 8(3 + x)(x + -3) Reorder the terms: 20x + 8x2 = 8(3 + x)(-3 + x) Multiply (3 + x) * (-3 + x) 20x + 8x2 = 8(3(-3 + x) + x(-3 + x)) 20x + 8x2 = 8((-3 * 3 + x * 3) + x(-3 + x)) 20x + 8x2 = 8((-9 + 3x) + x(-3 + x)) 20x + 8x2 = 8(-9 + 3x + (-3 * x + x * x)) 20x + 8x2 = 8(-9 + 3x + (-3x + x2)) Combine like terms: 3x + -3x = 0 20x + 8x2 = 8(-9 + 0 + x2) 20x + 8x2 = 8(-9 + x2) 20x + 8x2 = (-9 * 8 + x2 * 8) 20x + 8x2 = (-72 + 8x2) Add '-8x2' to each side of the equation. 20x + 8x2 + -8x2 = -72 + 8x2 + -8x2 Combine like terms: 8x2 + -8x2 = 0 20x + 0 = -72 + 8x2 + -8x2 20x = -72 + 8x2 + -8x2 Combine like terms: 8x2 + -8x2 = 0 20x = -72 + 0 20x = -72 Solving 20x = -72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '20'. x = -3.6 Simplifying x = -3.6
| x+7=x+50 | | (3a^2+2b^2)(4a^2-5b^2)=0 | | 9a^4+3a=0 | | x^2-8x+y^2-6y-11=0 | | x+3x+5=-3.5 | | 104(8)=3 | | 4x-5=4x | | 8x+3y=100 | | 4-(3x-5)=6 | | 8x^2-52x+80=0 | | 8(3y)=100 | | n=10-17 | | 0=5x(x^2-2x-1) | | 3x^2+2x+1=2x^2+16 | | (x+2)(x^2-2x+4)=0 | | b-5+5b=18 | | 8n-(5n+6)=15 | | 3x/4-x=2/3 | | .09k+.13(k+300)=61 | | 5-(t+3)=-1+2+3 | | 1.6(2t-1)=14.4 | | 36x^2-84xy+49y^2= | | -4(m+6)=3(m+6) | | (x+4)(3x^2-2x+5)=0 | | 9y+16-3y=-56 | | 5k-70=60 | | 0.003xwhat=3 | | 3*0.17x=1 | | 2(c-15)=62 | | 6(x-2)=8-2y | | -2x+7=11x-19 | | 5(x-4)-1=7x+3 |